An economic analysis of patient simulators for clinical training in nursing education. - Harlow KC; Sportsman S (Nursing Economic$)
Patient simulators have become widely used in medical education including increasing use in nursing education. Research suggests their usefulness in developing nursing competence. Little research to date, however, has examined the financial feasibility of the use of patient simulators as an educational tool. The extent to which a simulation lab comprising six Laerdal[TM] SimMan[TM] high-fidelity patient simulators and a staff of nurse educators is a financially feasible alternative to classroom-based education is examined.